Integrating Interactive Digital Technologies in Fine Arts Education: Enhancing Creativity and Engagement - Olimova Mohidil Sherzod qizi, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores the integration of interactive digital technologiesin fine arts education and their impact on student creativity, engagement, and artistic competencies. It examines the use of multimedia applications, animation software, virtual galleries, and online collaborative platforms to improve visual literacy and critical thinking. The study highlights pedagogical strategies such as project-based learning, flipped classrooms, and digital portfolios. Results indicate that technologyenhanced approaches foster individualized learning, active participation, and innovative artistic expression.